THE IPUMS COLLABORATION: INTEGRATING AND DISSEMINATING THE WORLD'S POPULATION MICRODATA. (20th May 2015) - Ruggles, Steven; McCaa, Robert; Sobek, Matthew; Cleveland, Lara
Abstract: The Integrated Public Use Microdata Series (IPUMS)-International partnership is a project of the Minnesota Population Center and national statistical agencies, dedicated to collecting and distributing census data from around the world. IPUMS is currently disseminating data on over a half-billion persons enumerated in more than 250 census samples from 79 countries. The data series includes information on a broad range of population characteristics, including fertility, nuptiality, life-course transitions, migration, labor-force participation, occupational structure, education, ethnicity, and household composition. This paper describes sample characteristics and data structure; the data integration process including the creation of constructed family interrelationship variables; the flexible dissemination system that enables researchers to build customized extracts of pooled census samples across time and place; and some of the most significant findings that have emerged from the database.